Pemerolehan Tindak Tutur Anak Penyandang Down Syndrom Pada Usia 11 Tahun: Kajian Psikolinguistik - Anggi Pelangi Sajrah; Sahla Annisa (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Communicating is important for individuals to be able to interact with other humans. Communication makes it easier for humans to convey ideas, ideas, messages, and so on. In communicating, humans create speech acts as a manifestation of the process of communication. In the study of psycholinguistics speech acts are also closely related to a person's psychological state. The surrounding environment and various nearby elements of course affect a person's development in the process of speaking since infancy. One of the obstacles can also be caused by limited physical conditions. For example in people with Down Syndrome. Most of people with this syndrome have difficulty pronouncing words, even speech delays. For this reason, in this discussion the author will discuss the stages of speech act development in children with Down Syndrome in accordance with psycholinguistic studies. This type of research is descriptive qualitative, namely to examine and describe speech acts in children with Down syndrome at the age of 11 years. Researchers obtained data through interviews using the face-to-face note-taking technique (CTS). The data used goes through the following stages: a.) Data processing; b.) results and discussion; c.) Conclusion.